EASYCHATBOT - Dias Barreto, Ana Júlia; Cappelle de Almeida, Breno; Wilson de Souza Rocha, José; Lamim Teodoro , Luan; Mendes de Oliveira, Luiz Fellipe; Oliveira Gomes Melo, Vitoria (CIPEEX, 2024)
"We are EasyChatBot, a startup that is revolutionizing the way companies communicate with their customers. Our platform allows users to create and customize their own chatbots easily and intuitively. Our user-friendly application enables users to create their own custom chatbots in minutes, without the need for programming knowledge. They can choose from a variety of templates and personalize them with their unique brand, voice, and tone. Furthermore, our platform offers integrations with leading marketing automation and CRM tools in the market, allowing users to automate the entire customer journey."